(untitled) (Research, Society and Development, 2021)
The main aim of this paper is to identify responsible custody’s profile of cats and dogs in Maringá, Paraná. Brazil and measure its correlation with the socioeconomic profile of the interviewees. For that, 395 interviews were made, each containing six questions to measure socioeconomic profile and fifteen to measure the responsible custody profile. It was observed that 56.5% of the interviewees were female. Independing on gender, interviewees resided mostly on houses, aged from 20 to 30 years old, had completed superior education and had an income of two to five minimum wages. As to the responsible custody profile, 86.8% had pets, being 75.8% having only dogs, 14.3% having cats and dogs and 7.9% having only cats. It was observed that 58.3% had not neutered their pets and from those, 43.9% had free outdoors access, opposed to interviewees that had neutered their pets (27.1%) and had free outdoors access (34.1%). The use of dog food is administered from a majority of the interviewees and had no correlation to family income and education level. A high percentage of the interviewees stated to vaccine their pets (75%) and gave vermicides (73.5%). Interviewee income is an important factor in relation to doctor appointments frequency. It follows that the different aspects of responsible care in the city of Maringá lacks of attention from awareness campaigns for population control, free outdoors access and neutering programs, as new studies, to clarify other aspects of responsible custody in the region.